HUBUNGAN JARAK TEMPUH DENGAN KADAR SISA CHLOR BEBAS DAN MPN COLIFORM DI PDAM RESERVOIR MEDINI KUDUS - Noor Zahrotul Muniroh; Nurjazuli Nurjazuli; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Clean Water as main source to all living thing. Getting clean water which having good quality close to drink water quality must having treatment before. PDAM Kudus as a water provider company based on drink water quality according to the policy of Minister of Health Regulation No.492 of 2010 about requirements and supervision drink water quality. The aims of this study is to knowing the relation between water mileage to free chlorine residual level and MPN Coliform in PDAM Undaan District Medini’s reservoir region.The design of this study was Cross Sectional with the type of observational analytic (quantitative) with affordable population and Lemeshow formula technique got 42 customers sample plus 1 Medini reservoir. Normality test used Shapiroo Wilk, then to analyze the relation used Rank Spearman because unnormal distribution. The result showed that there were 13 samples (30,2%) positive contained coliform bacteria. 2 (two) samples of them containing coliform for about ≥240 per 100 ml at 7650 meters and 8000 meters. The level of free chlorine residual was over at ≥7000 meter. The average of free chlorine residual was 0,22 mg/l with maximum value was 0,9 mg/l, while pH and temperature each of them were 7,3 and 29,3 ͦC. Statistic test with significant α: 0,05 and p value was 0,0001 showed that there was a relation between water mileage to free chlorine residual and there was a relation between free chlorine residual to MPN Coliform in PDAM Undaan district Medini’s reservoir region. Suggestion advice may be giving optimal chlorine and provide chlorination pos in certain distance to reach fartest region distribution.